Implementation of an ARM-based system using a Xilinx ZYNQ SoC - Omar Salem Baans; Asral Bahari Jambek (Institute of Advanced Engineering and Science, 2019)
ARM processors are widely used in embedded systems. They are often implemented as microcontrollers, field-programmable gate arrays (FPGAs) or systems-on-chip. In this paper, a variety of ARM processor platform implementations are reviewed, such as implementation into a microcontroller, a system-on-chip and a hybrid ARM-FPGA platform. Furthermore, the implementation of a specific ARM processor, the Cortex-A9 processor, into a system-on-chip (SoC) on an FPGA is discussed using Xilinx’s Vivado and SDK software system and execution on a Xilinx Zynq Board.